Efecto de la corrupción en el desarrollo humano: evidencia empírica por grupos de países usando técnicas de datos de panel, 1995-2017” - Jumbo Obaco, María Belén (2020)
The objective of this research is to answer the question does corruption affect human development? Both globally and in a group of countries. Updated data from the panel of 55 countries for the period 1995 - 2017. The dependent variable was the Human Development Index (HDI) and the independent variable was the Government Integrity Index, and it also included 3 control variables. We classify countries into three groups: high income (PIA), upper middle income (PIMA), and lower middle income (PIMB). The results that determine the effect of government integrity on the Human Development Index are statistically significant and positive, both globally and in high-income and upper-middle-income countries (PIMA). With control variables, the integrity of the government maintains its positive and statistically significant effect both at the GLOBAL, PIA and PIMA levels, in addition to the other groups of countries, the significance is nil. As policy implications, it is necessary to formulate policies that require a more rigorous control of the activities of the central government, so that there are no diversions of state resources, governments can also promote legislative reforms to establish legal and institutional frameworks against corruption that includes strong punitive measures. The media should be used as a check against the participation of governments and the private sector in corrupt practices.